Evolution of SARS-CoV-2 in the Rhine-Neckar/Heidelberg region 01/2021-07/2023 - Bundschuh, Christian; Weidner, Niklas; Klein, Julian; Rausch, Tobias; Azevedo, Nayara; Telzerow, Anja; Mallm, Jan-Philipp; Kim, Heeyoung; Steiger, Simon; Seufert, Isabelle; Börner, Kathleen; Bauer, Katharina; et al. (Infection, genetics and evolution, 2024)
In January 2021, the monitoring of circulating variants of SARS-CoV-2 was initiated in Germany under the Corona Surveillance Act, which was discontinued after July 2023. This initiative aimed to enhance pandemic containment, as specific amino acid changes, particularly in the spike protein, were associated with increased transmission and reduced vaccine efficacy. Our group conducted whole genome sequencing using the ARTIC protocol (currently V4) on Illumina's NextSeq 500 platform (and, starting in May 2023, on the MiSeq DX platform) for SARS-CoV-2 positive specimen from patients at Heidelberg University Hospital, associated hospitals, and the public health office in the Rhine-Neckar/Heidelberg region. In total, we sequenced 26,795 SARS-CoV-2-positive samples between January 2021 and July 2023. Valid sequences, meeting the requirements for upload to the German electronic sequencing data hub (DESH) operated by the Robert Koch Institute (RKI), were determined for 24,852 samples, and the lineage/clade could be identified for 25,912 samples. The year 2021 witnessed significant dynamics in the circulating variants in the Rhine-Neckar/Heidelberg region, including A.27.RN, followed by the emergence of B.1.1.7 (Alpha), subsequently displaced by B.1.617.2 (Delta), and the initial occurrences of B.1.1.529 (Omicron). By January 2022, B.1.1.529 had superseded B.1.617.2, dominating with over 90%. The years 2022 and 2023 were then characterized by the dominance of B.1.1.529 and its sublineages, particularly BA.5 and BA.2, and more recently, the emergence of recombinant variants like XBB.1.5. Since the global dominance of B.1.617.2, the identified variant distribution in our local study, apart from a time delay in the spread of new variants, can be considered largely representative of the global distribution. om a time delay in the spread of new variants, can be considered largely representative of the global distribution.